Representasi Feminisme Radikal dalam K-Drama sebagai Resistensi Budaya Patriarki - Novianty, Suci Marini (Jurnal Mahardika Adiwidia, 2024)
This study examines the representation of radical feminism in the South Korean drama "Love to Hate You." Using a qualitative approach with a critical paradigm, the research employs Sara Mills' critical discourse analysis to understand how language and text structure create representations of women in the drama. The analysis aims to unveil how radical feminist values are reflected in dialogues, actions, and character relationships in the drama. The findings of the study suggest that the drama "Love to Hate You" provides a complex and nuanced representation of radical feminism. On the one hand, the drama portrays the protagonist, Yeo Mi Ran, as a strong and independent woman who resists patriarchal norms. Mi Ran rejects marriage, childbirth, and romantic relationships, and she pursues a career in law. On the other hand, the drama also shows how Mi Ran is still subject to patriarchal stereotypes and expectations. For example, Mi Ran is often portrayed as being cold and unemotional, and she is criticized for her lack of femininity. Overall, the study argues that the drama "Love to Hate You" provides a valuable contribution to the understanding of radical feminism in South Korean culture. The drama challenges traditional stereotypes about women, and it portrays a complex and multifaceted image of a radical feminist.